Policy of Collective West on Military Assistance to Ukraine - Мазурок, Володимир; Сидорук, Тетяна (Київський національний університет імені Тараса Шевченка, 2025)
Since the beginning of russia's aggression against Ukraine in 2014, and especially after the full-scale invasion in 2022, the policy of the Collective West on military assistance to Ukraine has undergone a significant transformation. The article systematically analyzes the evolution of the leading Western countries' (NATO, EU, G7) approaches to supporting Ukraine in the military and defense sphere in 2014-2025. The main stages of change are identified: from symbolic non-lethal support to large-scale supplies of modern weapons and training. The motivating factors of the West's policy - geopolitical interests, principles of international law, humanitarian obligations, internal political dynamics and the threat of revisionism - are investigated. Special attention is paid to institutional mechanisms of coordination and the influence of public opinion, media and economic factors on decision-making. It is concluded that military assistance to Ukraine has become not only a tool for responding to the crisis, but also an important factor in the formation of a new Euro-Atlantic security architecture, in which Ukraine is an active actor in the transformation of regional security.

Від початку агресії росії проти України у 2014 році, а особливо після повномасштабного вторгнення 2022 року, політика Колективного Заходу щодо військової допомоги Україні зазнала суттєвої трансформації. У статті системно проаналізовано еволюцію підходів провідних країн Заходу (НАТО, ЄС, G7) до підтримки України у військово-оборонній сфері в 2014–2025 роках. Визначено основні етапи змін: від символічної нелетальної підтримки до масштабного постачання сучасного озброєння та підготовки кадрів. Досліджено мотиваційні чинники політики Заходу — геополітичні інтереси, принципи міжнародного права, гуманітарні зобов’язання, внутрішньополітичну динаміку та загрозу ревізіонізму. Окрему увагу приділено інституційним механізмам координації та впливу громадської думки, медіа й економічних факторів на ухвалення рішень. Зроблено висновок, що військова допомога Україні стала не лише інструментом реагування на кризу, а й важливим чинником формування нової євроатлантичної безпекової архітектури, у якій Україна виступає активним суб’єктом трансформації регіональної безпеки.
Політика колективного заходу щодо військової допомоги Україні
Keywords: military assistance; Collective West; Ukraine; NATO; security policy; full-scale invasion; Euro-Atlantic security; військова допомога; Колективний Захід; Україна; НАТО; безпекова політика; повномасштабне вторгнення; євроатлантична безпека